FORMULASI MINUMAN TEPUNG CACING TANAH (Lumbricus rubellus Hoffmeister) TERGANULASI DISERTAI UJI DAYA INGATNYA PADA MENCIT JANTAN - Gita Cahya Eka Darma; Wulandari Putri Saraswati; Esti Rachmawati Sadiyah (Jurnal Ilmiah Farmasi Farmasyifa, 2018)
Protein is a chemical compound that is important for body. Earthworm (Lumbricus rubellus Hoffmeister) is known to have high protein content that can be used as alternative protein. This study aimed to determine the activity of earthworm flour in improving memory on mice (Mus musculus) and its formulation in the form of granulated earthworm flour beverage. Memory activity test was performed using Y labyrinth with observation parameter in the form of latency time (second) and number of errors. The optimum dose resulted from the memory test is 325 mg/kg BB which is equivalent to the use of two times the preparation containing 1.25 g of earthworm flour. Optimization of suspending agent was done singly and combination and obtained 3 formulae combination of best suspending agent and then continued to granulation proces. Formula evaluation conducted were organoleptic test, moisture, flow properties, particle size distribution, reconstitution time, redispersion time, sedimentation volume, viscosity, stability, hedonic test and quantitative analysis of protein content. Based of evaluation, one optimum formula was chosen which was, combination of 0,5% CMC-Na, 0,1% Sodium Alginate, 3,75% turmeric powder, 10% white sugar, 3% talk and Mg stearat 1%. The protein contained in the best formula was 26.03%